Natural Sciences in Archaeology and Cultural Heritage - Liritzis, Ioannis (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
A Special Issue of the international journal Sustainability under the section Sustainability of Culture & Heritage has been made, entitled Natural Sciences in Archaeology and Cultural Heritage. The bridge between science/technology and the humanities (archaeology, anthropology, history of art, and cultural heritage) has formed a well-established interdisciplinary subject with several sub-disciplines; it is growing exponentially, spurred by the fast development of technology in other fields (space exploration, medical, military, and industrial applications). On the other hand, art and culture struggle to survive due to neglect, lack of funding, or the dangers of events such as natural disasters and war. This volume strengthens and exerts the documentation of the sustainability of the issue that arises from the outcome of resulting research and the application of such a duality link. The sustainable dimension emerges from society, education, and economics through the impact of cultural growth, all of which produce a balanced society, in which prosperity, harmony, and development are merged at a sustainable local/regional/national/social level. A wide range of subjects linking the applied natural sciences with archaeology and the cultural heritage of innovative research and applications are presented in this volume.